(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Optimizing business processes in the era of digital transformation is one of the important tasks for every organization today. Innovations such as digital technologies, artificial intelligence, big data and cloud services are creating new opportunities for organizations. This article provides information on the importance, methods and practices of business process optimization during digital transformation.